2021
DOI: 10.1149/1945-7111/ac0603
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Properties of Indium-Gallium-Zinc-Oxide Thin Films under the Influence of Thickness and Annealing Ambient

Abstract: In this study, indium-gallium-zinc-oxide (IGZO) thin films were investigated for detection of Nitrogen Dioxide (NO2) gas. IGZO films with a thickness range of 25–100 nm were deposited using IGZO (ZnO: Ga2O3:In2O3 = 1:1:1 mol.%) polycrystalline target on interdigitated Au electrode alumina substrates and annealed in different annealing atmosphere of Nitrogen (N2) and Oxygen (O2). The effects of the IGZO thickness and different annealing ambient on IGZO were investigated on sensing properties. The N2 ambient sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The energy gaps of InO and SnO 2 materials are 3.2 eV and 3.6 eV, 19 respectively. According to the research of others, 20,21 InO and SnO 2 will interact with NO 2 , NO, and O 3 reducing gases. A reaction is generated, thereby increasing the resistivity of the sensor to achieve the effect of sensing gas.…”
mentioning
confidence: 96%
“…The energy gaps of InO and SnO 2 materials are 3.2 eV and 3.6 eV, 19 respectively. According to the research of others, 20,21 InO and SnO 2 will interact with NO 2 , NO, and O 3 reducing gases. A reaction is generated, thereby increasing the resistivity of the sensor to achieve the effect of sensing gas.…”
mentioning
confidence: 96%
“…It means 100 nm IGZO can absorb 63% of incident photons. Thicker IGZO layer results in reduced mobility and increased roughness [157][158][159] , therefore 150 nm IGZO was chosen to ensure sufficient absorption of UV irradiation in IGZO. Wang et al [142] found that the GaAs nanowire/nanocone structure with a diameter of ~400-600 nm and height of ~400-600 nm shows outstanding light absorption performance.…”
Section: Nanopillar Gaasmentioning
confidence: 99%